2021
DOI: 10.3892/ijmm.2021.4945
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs in colorectal cancer: Overcoming barriers of the metastatic cascade (Review)

Abstract: The journey of cancer cells from a primary tumor to distant sites is a multi-step process that involves cellular reprogramming, the breaking or breaching of physical barriers and the preparation of a pre-metastatic niche for colonization. The loss of adhesion between cells, cytoskeletal remodeling, the reduction in size and change in cell shape, the destruction of the extracellular matrix, and the modification of the tumor microenvironment facilitate migration and invasion into surrounding tissues. The promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…Metastatic malignant breast cancer accounts for 20–30% of breast cancer cases and the survival rate of the disease is only 22%, making it the leading cause of death for patients [ 5 , 25 , 26 ]. Metastatic spread of breast cancer involves many steps, including EMT, migration, invasion, extravasation, mesenchymal–epithelial transformation (MET) and colonisation [ 27 ]. An increasing range of research has demonstrated the importance of exosomes for all metastatic processes such as migration invasion of cancer [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic malignant breast cancer accounts for 20–30% of breast cancer cases and the survival rate of the disease is only 22%, making it the leading cause of death for patients [ 5 , 25 , 26 ]. Metastatic spread of breast cancer involves many steps, including EMT, migration, invasion, extravasation, mesenchymal–epithelial transformation (MET) and colonisation [ 27 ]. An increasing range of research has demonstrated the importance of exosomes for all metastatic processes such as migration invasion of cancer [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal microRNAs play pivotal pro- and anti-tumoral roles in CRC progression and metastasis. They could also serve as biomarkers of CRC progression in patients ( 96 , 97 ). On one hand, exosomal miR-21 promotes CRC cell proliferation, invasion, and therapy resistance ( 98 ).…”
Section: Non-cellular Componentsmentioning
confidence: 99%
“…EV-mediated intracellular communication plays a role not only in maintaining cell homeostasis, but also in disease progression [ 96 , 97 , 98 , 99 ]. Exosomes are associated with several diseases, including cancer metastasis, which is the invasion and spread of primary cancer cells into other organs [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]. Exosomes have been shown to play an important role in the formation of the cancer microenvironment and the mechanisms of cancer malignancy, such as cancer cell growth, infiltration, metastasis, and pre-metastasis niche [ 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ].…”
Section: Evs In Cancer Metastasis and Malignant Transformationmentioning
confidence: 99%